Ruled Play Is A Means Of Harmonious Development Of Children - Umarova Mehriniso Ibragim kizi (Academia One Publishing, 2024)
Modern psychology and pedagogy are faced with the task of developing scientific foundations for the development of preschool children for the maximum use of all types of activities and interactions with adults and peers.
Keywords: Ruled play; children; information